Special subject teachers need more support to mitigate respiratory viral spread in schools: insights from interviews during COVID-19. - Amoh-Asante, Nana Adwoa Akuffo; Lowe, Ashley A; Wilson, Amanda M (Annals of Work Exposures & Health, 2026)
This commentary describes the real-world challenges special subject teachers faced while implementing coronavirus disease-2019 (COVID-19) mitigation strategies recommended by the Centers for Disease Control and Prevention (CDC) in Kindergarten- 5th grade classrooms in a school district in Pima County, Arizona, during the 2021 to 2022 academic year and argues for better support for special subject teachers. While teachers in all classroom types experienced challenges, special subject teachers (eg, special education, physical education, and English as a Second Language [ESL]) faced additional barriers to implementing recommended CDC COVID-19 guidelines. In special education classrooms, the constant need for close physical assistance made social distancing from students impossible. Additionally, mask mandates posed choking and saliva-related safety concerns for students, making it difficult for teachers to enforce the mandate. For ESL teachers, implementing the mask mandate meant losing out on using visemes and visual cues, which are an integral part of ESL instruction. In physical education, rigorous disinfection routines between students led to the rapid degradation of gym equipment and heightened concerns about chemical exposure. We reflect on the challenges and modifications these teachers faced, highlighting classroom-specific examples and illustrative quotes from key informant interviews. Future policies and guidance that better support the health of teachers and effective infection control across various classroom environments will benefit from educator collaboration and input.